Role Playing as a Teaching Strategy for Achieving University Student Competencies (Docentes 2.0 Journal, 2025)
In contemporary global development, humanity faces constant transformations and adapts its practices to new environments through formal education. This study aimed to identify the competencies and skills that role-playing, conceived as a didactic strategy, promotes in university students from diverse scientific fields. The research was conducted under the positivist paradigm, using a hypothetical-deductive method, a quantitative approach, a quasi-experimental design, and an explanatory, cross-sectional approach. Fifty-six studies located in EBSCOhost, SciELO, Redalyc, and Dialnet, published between January 2015 and December 2024, were analyzed. These studies focused on role-playing as the main variable. The results showed that the most strongly developed generic competencies include interpersonal skills, social skills, teamwork, critical analysis, and decision-making. Other competencies varied across scientific fields, while specific competencies were closely linked to each academic program.
Keywords: Strategies; competencies; role play; professionals; university students